ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE PROFIL RISIKO, TATA KELOLA PERUSAHAAN YANG BAIK, PENDAPATAN & MODAL (Studi Komparasi Antara Bank Umum Konvensional dan Bank Umum Syariah Di Indonesia Lemabaga yang Terdaftar Pada Otoritas Layanan Keuangan - Gusganda Suria Manda; Rina Maria Hendriyani (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
This analysis aims to find out, analyze and explain how the bank's soundness level compares with the Risk Profile, Good Corporate Governance, Earning and Capital methods in accordance with applicable regulations. This research was conducted using a comparative descriptive method with a quantitative approach. The results of the analysis of this study the authors get that Conventional Commercial Banks have a Risk Profile (NPL ratio) with a rating of "Good" better than a Sharia Commercial Bank with a rating of "Fairly Good". Conventional Commercial Banks have a Risk Profile (LDR) higher than Islamic Commercial Banks with a rating of "Fairly Good". Conventional Commercial Banks have Good Corporate Governance (GCG) better than Sharia Commercial Banks with a "Good" rating. Conventional Commercial Banks have better Earning (ROA) with a "Very Good" rating than a Sharia Commercial Bank with a "Very Poor" rating. Sharia Commercial Banks have a Capital (CAR) higher than Conventional Commercial Banks with a rating of "Very Good